2015
DOI: 10.1016/j.jas.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Postclassic Petén Maya bow-and-arrow use as revealed by immunological analysis​

Abstract: 6The bow-and-arrow was a widely used weapon in the Postclassic and Contact periods in the 7Maya lowlands. A sample of 108 arrow points from varied archaeological contexts in the lakes 8 region of central Petén, northern Guatemala, was submitted for cross-over 9 immunoelectrophoresis (CIEP) analysis. Analysis resulted in 25 positive matches to available 10 antisera for a wide range of local and introduced fauna, from small and large land mammals to 11 avians. These findings indicate possible uses in subsistence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Estimating the degree of inter-Maya conflict from point assemblages is difficult because most projectiles were likely used for hunting. For example, previous immunological testing of 108 projectiles from Peten revealed that of the 37 immunological positives to fauna, only two tested positive for human protein—accounting for just 5.4 percent of the sample (Meissner and Rice 2015). Additionally, obsidian blades (prior to being reduced into points) played an essential role in bloodletting and autosacrifice, which could leave similar residue (Stemp 2016; Stemp et al 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimating the degree of inter-Maya conflict from point assemblages is difficult because most projectiles were likely used for hunting. For example, previous immunological testing of 108 projectiles from Peten revealed that of the 37 immunological positives to fauna, only two tested positive for human protein—accounting for just 5.4 percent of the sample (Meissner and Rice 2015). Additionally, obsidian blades (prior to being reduced into points) played an essential role in bloodletting and autosacrifice, which could leave similar residue (Stemp 2016; Stemp et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This article examines these identities from a technological perspective of projectile weaponry that includes elements of vertical (generational) and horizontal (contact-related) transfer in lithic technology. Small arrow points are a defining class of stone tool during the Late Postclassic to Early Colonial (Contact) periods (Figure 2), and have been studied at several sites in the Maya region (Aoyama 2005; Blake 2010; Graham 1991, 2011; Marino et al 2016; Masson 2000; Meissner 2014, 2017, 2018a; Meissner and Rice 2015; Oland 2013; Proskouriakoff 1962; Shafer and Hester 1988; Simmons 1995, 2002).
Figure 1.Map of the modern Peten-Belize border with approximate locations of ethnopolities, and major Late Postclassic/Colonial period sites.
…”
Section: Introductionmentioning
confidence: 99%
“…The most common siliceous tools were bifaces and small, triangular side-notched projectile points (<3 cm in length, <1 g in weight) with either short or elongated blades (Meissner 2014). Such points, common throughout LPC Mesoamerica, are associated with bow-and-arrow technology (Andresen 1976; Meissner and Rice 2015; Shafer and Hester 1988; Thomas 1978). Obsidian tools were primarily prismatic blades; despite these patterns, obsidian points seem to have played a special political-economic role (Chase 1992:123).…”
Section: Exploring Market Restriction In Postclassic Mesoamericamentioning
confidence: 99%
“…A different perspective on faunal use Group 719 comes from crossover immuno-electrophoresis (CIEP) analysis of animal protein (blood) residues on two projectile points from temple Structure 721 (Meissner and Rice 2015). Both points were of San Martín Jilotepeque obsidian.…”
Section: Faunamentioning
confidence: 99%